The Impact Of-Problematic Learning Styles-On Learning Outcomes Of Cultural Diversity In My Country 1 Sub-Diameter 1 Unity - Dzulfiqar Falah, Reza; Budiana, Sandi; Sri Indriani, Rini (Journal of International Multidisciplinary Research, 2024)
The Impact of Problematic Learning Styles on Learning Outcomes in My Country Cultural Diversity Teachers and Teaching Education Dissertation Pacuan University. 2566 This study is a quasi-experimental study using traditional and problem-based learning models to investigate how cultural diversity sub-factors affect learning outcomes in My Country State School in Bokor IV C 78 Problem-based learning models have more requirements than traditional control class learning problems based on the experimental class model compared to the model. Because the results of both samples are lower than the L table, they have a high N value, so to find out whether the sample <0.148 is distributed in normal class groups, the researcher conducted an additional normality test using the Liliefors test hypothesis test of 7.42843 is greater than 1.9944 in the table, therefore the alternative hypothesis is accepted and the null hypothesis H0 is rejected Based on the above findings, the problem-based learning model is more effective than the traditional approach. diversity in my country.